Sprawozdawczość finansowa banku jako baza informacyjna controllingu - Dyduch, Alina (Financial Reporting of Bank as Information Base of Controlling, 2007)
The article presents elements of financial reporting of a bank: balance sheet, profit and loss account, cash flows and other reports. The data obtained from these reports are the information base of controlling. Particularly indicators of financial analysis and their usefulness for controlling are discussed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 121-129